Novel reed + deep eutectic solvent-derived adsorbents for recyclable and low-cost capture of dyes and radioactive iodine from wastewater. Issue 10 (7th September 2022) - Chen, Yu; Liu, Zhenghui; Li, Yuting; Tong, Jie; Guo, Yuting; Bi, Zixin; Yang, Xiaoqing; Wang, Han; Wang, Jianqiang; Zhao, Di
Abstract : Deep eutectic solvent-based adsorbents are found to capture radioactive iodine and dyes from wastewater with high efficiency and high recyclability. Abstract : Green and low-cost capture of radioactive iodine is urgently needed due to nuclear leaks and nuclear disasters. Deep eutectic solvents (DESs) are deemed as green solvents of the 21st century with high biocompatibility, high atom efficiency and high tunability. However, DESs used for the capture of radioactive iodine are hardly recyclable, leading to undesirable environmental pollution and high cost. Here, green and low-cost capture of radioactive iodine from wastewater is achieved using novel DES-derived adsorbents. The results show that the DES-derived adsorbents could improve the removal efficiency (>99%) of radioactive iodine and achieve recyclable utilization compared to reported DESs for iodine capture. Other pollutants in wastewater could also be efficiently removed by the DES-derived adsorbents. This work provides a green strategy for the sustainable and recyclable treatment of radioactive iodine with high efficiency using novel DES-derived adsorbents.